High frequency of telomerase reverse-transcriptase promoter somatic mutations in hepatocellular carcinoma and preneoplastic lesions - Nault, Jean Charles; Mallet, Maxime; Pilati, Camilla; Calderaro, Julien; Bioulac-Sage, Paulette; Laurent, Christophe; Laurent, Alexis; Cherqui, Daniel; Balabaud, Charles; Zucman-Rossi, Jessica (Nature communications, 2013)
Somatic mutations activating telomerase reverse-trancriptase promoter were recently identified in several tumour types. Here we identify frequent similar mutations in human hepatocellular carcinomas (59%), cirrhotic preneoplastic macronodules (25%) and hepatocellular adenomas with malignant transformation in hepatocellular carcinomas (44%). In hepatocellular tumours, telomerase reverse-transcripase- and CTNNB1 -activating mutations are significantly associated. Moreover, preliminary data suggest that telomerase reverse-trancriptase promoter mutations can increase the expression of telomerase transcript. In conclusion, telomerase reverse-trancriptase promoter mutation is the earliest recurrent genetic event identified in cirrhotic preneoplastic lesions so far and is also the most frequent genetic alteration in hepatocellular carcinomas, arising from both the cirrhotic or non-cirrhotic liver. Telomerase reverse-trancriptase promoter mutations have been recently found in human melanomas. Here, Nault et al. identify telomerase reverse-trancriptase promoter mutations as the most frequent somatic genetic alterations in hepatocellular carcinomas and as the first mutation identified in cirrhotic preneoplastic lesions.